Investments in Agricultural Machinery and its Efficiency in Ukraine - Stavytskyy, Andriy; Prokopenko, Oleksandra (Ekonomika, 2017)
One of the major conditions of effective agriculture production is sufficient farm mechanization. However, the unstable economic situation in Ukraine, combined with bureaucratic problems, an unstable currency exchange rate, and sharply changed trade routes (which has caused major losses to a number of farms and traders working with the Custom Union) created significant obstacles for investing in machinery in Ukraine. It is especially topical for small and medium farms that usually function in poor economic conditions without any adequate access to the credit market. Consequently, Ukrainian agriculture producers often have an inadequate mechanization rate. As a result, the productivity of Ukrainian farms is significantly lower as compared to other countries that have similar natural conditions in terms of temperatures, precipitation and quality of agricultural lands.A no less important problem is the lack of awareness of small and medium farms, which may not realize the effect that investment has in agriculture machinery. Thus, in order to provide specific numbers for potential investors and prove the efficiency of this fund placement, an expected direct economic effect from machinery investment (as an increased profit from higher yield) was estimated. The first step was to define those types of agricultural machinery that have significant impact on the yield and productivity levels for each of the most important crop types: grain, oil crops, vegetables, fruits, etc. Then, an impact of additional investment in various machinery means on crops yield was estimated. Finally, based on fixed prices and a discount rate, an expected additional profit generated by newly purchased machinery on an average farm was estimated. The model proved especially high profitability of investment in such machinery as ploughs, fertilizers spreaders, harvesters, tractors, and machines for irrigation – most of them are paid off (on a land parcel with area around 2000 ha) in three years or less.
Keywords: agriculture mechanization; MANOVA; stochastic frontier analysis; investment; mechanization rate